Pharmacokinetic And Pharmacodynamic Modeling Of Mitragynine In PainTolerance - Ramachandram, Dinesh Sangarran (2020)
Mitragyna speciosa, also known as ‘Ketum’or ‘Biak-biak’ in Malaysia and Kratom in Thailand, is a native plant to Southeast Asia. It has a long history of folk medicine use in Southeast Asia and recently has gained popularity in Western countries. Mitragynine (MG) is the principal alkaloid found in the leaves of Mitragyna speciosa and has been reported to be responsible for the plant’s therapeutic actions. Pain relief is among many self-reported beneficial kratom effects. However, there have not been any controlled clinical studies reported on the analgesic property of Ketum employed a standardized formulation. The objective of this study is to evaluate the PKPD of mitragynine in human subjects. In view of this, work was undertaken in Universiti Sains Malaysia to scientifically assess the pain relief effects of Ketum decoction in a randomized, double-blind, placebo- controlled study. Ketum and placebo decoctions were prepared and standardized as a formulation to be administered to the subjects in the clinical study.